EFFICIENCY OF ORGANIC WASTE RECYCLING THROUGH VERMICOMPOSTING PROCESS (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
The agricultural sector and growing food production needs relies on chemical fertilizers. This initially had positive effects on production, but over the last decade the negative impacts of overuse have resulted in low crop productivity, increased pest and disease infestation, soil degradation and consequent adverse effects on environmental parameters. As one of the possibilities in organic farming we found vermicomposting as the more sustainable practice. For the assembly of vermicomposting, mature cattle manure was utilized in three different combinations with organic material and earthworms inoculations (the household waste, the grass clippings and mixture). The experiment was set up by random block design in three replications. Analyzes of qualitative parameters of final product showed a pH reaction neutral to slightly alkaline. The nitrogen compound varied between 2.7-2.9 %, while organic carbon varied between 45.59-47.41% showing a C/N ratio of 16.7-16.67. The potassium content varied between 1.1-1.2% K2O and phosphorus from 0.3-0.5%. The experiment indicates quite good results of vermicomposting of household waste with manure, showing a neutral pH reaction optimal content of ash and carbon with almost similar and good NPK contents and increased C/N ratio of 16.7 and with satisfying trace elements content and heavy metal contents under the limits. These results indicate that vermicomposting can increase quality of final product.